Adver-Where? Comparing the Effectiveness of Banner Ads and Video Ads in Online Video Games. Issue 2 (2nd July 2016) - Dardis, Frank E.; Schmierbach, Mike; Sherrick, Brett; Waddell, Frank; Aviles, Jose; Kumble, Sushma; Bailey, Erica
ABSTRACT: Banner ads, video ads, and advergames constitute a large portion of online gaming spending, yet no prior research has incorporated them simultaneously to determine if any separate or joint effects exist, and if so to what extent. Therefore, two experiments were conducted to test the effects of ad types on brand recall and attitude within two different but very common game settings (advergame or nonbranded game). Study 1 found that preroll video ads outperformed banner ads quite robustly in the nonbranded game, but these effects dissipated in the advergame. Building on these findings, Study 2 manipulated the location of video ads. The midroll ad position was more influential than the preroll and no-ad conditions, followed by the postroll position, thereby indicating a modest pattern of recency effects, especially in the nonbranded game. Theoretical and practical implications are discussed.